Mouse pulmonary response to dust from sawing Corian®, a solid-surface composite material. Issue 11 (3rd June 2019) - Mandler, W. Kyle; Qi, Chaolong; Orandle, Marlene S.; Sarkisian, Khachatur; Mercer, Robert R.; Stefaniak, Aleksandr B.; Knepp, Alycia K.; Bowers, Lauren N.; Battelli, Lori A.; Shaffer, Justine; Friend, Sherri A.; Qian, Yong; et al.
ABSTRACT: Corian®, a solid-surface composite (SSC), is composed of alumina trihydrate and acrylic polymer. The aim of the present study was to examine the pulmonary toxicity attributed to exposure to SSC sawing dust. Male mice were exposed to either phosphate buffer saline (PBS, control), 62.5, 125, 250, 500, or 1000 µg of SSC dust, or 1000 µg silica (positive control) via oropharyngeal aspiration. Body weights were measured for the duration of the study. Bronchoalveolar lavage fluid (BALF) and tissues were collected for analysis at 1 and 14 days post-exposure. Enhanced-darkfield and histopathologic analysis was performed to assess particle distribution and inflammatory responses. BALF cells and inflammatory cytokines were measured. The geometric mean diameter of SSC sawing dust following suspension in PBS was 1.25 µm. BALF analysis indicated that lactate dehydrogenase (LDH) activity, inflammatory cells, and pro-inflammatory cytokines were significantly elevated in the 500 and 1000 µg SSC exposure groups at days 1 and 14, suggesting that exposure to these concentrations of SSC induced inflammatory responses, in some cases to a greater degree than the silica positive control. Histopathology indicated the presence of acute alveolitis at all doses at day 1, which was largely resolved by day 14. Alveolar particle deposition and granulomatous mass formation were observed in all exposure groups at day 14. The SSC particles were poorly cleared, with 81% remaining at the end of the observation period. These findings demonstrate that SSC sawing dust exposure induces pulmonary inflammation and damage that warrants further investigation. Abbreviations: ANOVA: Analysis of Variance; ATH: Alumina Trihydrate; BALF: Bronchoalveolar Lavage Fluid; Dpg : Geometric Mean Diameter; FE-SEM: Field Emission Scanning Electron Microscopy; IACUC: Institutional Animal Care and Use Committee; IFN-γ: Interferon Gamma; IL-1 Β: Interleukin-1 Beta; IL-10: Interleukin-10; IL-12: Interleukin-12; IL-2: Interleukin-2; IL-4: Interleukin-4; IL-5: Interleukin-5; IL-6: Interleukin-6; KC/GRO: Neutrophil-Activating Protein 3; MMAD: Mass Median Aerodynamic Diameter; PBS: Phosphate-Buffered Saline; PEL: Permissible Exposure Limit; PM: Polymorphonuclear Leukocytes; PNOR: Particles Not Otherwise Regulated; SEM/EDX: Scanning Electron Microscope/Energy-Dispersive X-Ray; SSA: Specific Surface Area; SSC: Solid Surface Composite; TNFα: Tumor Necrosis Factor-Alpha; VOC: Volatile Organic Compounds; σg : Geometric Standard Deviation.